Training in gastroenterology in the south west: results of a survey of trainees and training leads. (13th March 2011) - Arthurs, E A; Mehta, T; Hare, N; Sieberhagen, C; Pugh, S; Lockett, M
Abstract : Introduction: Feedback on training posts is collected by a variety of different sources; individual deaneries, PMETB and the Royal College of Physicians. The quality panel for gastroenterology training was developed to review the quality of training in the region. The panel found feedback on training posts to be of variable quality, incomplete, and difficult to analyse. The aim was to create a specific, reproducible method of assessing gastroenterology and general internal medicine (GIM) training, to provide feedback on individual posts in order to inform the training committee, quality panel, and the deanery and facilitate improvements in training. Methods: A questionnaire was designed comprising 55 questions within 7 domains of gastroenterology training. The questions were determined based on previous surveys and other areas of importance according to consensus of consultant and trainee opinion. It was emailed to all registrars and training leads in the Severn and Peninsula deaneries. Data was collected anonymously for the last 3 years of training. Answers correlated to a numerical score, with high scores correlating with high quality. Mean scores were calculated per domain, per trust; a total score was then calculated. Differences between the mean trainee and training lead scores were calculated. The data was presented to the quality panel and the training committees. Individual feedback was given to each trust. Results: 59 anonymised responses were received from trainees for all 14 hospitals within the South West region. Responses by trust varied from 3 to 9. 10 responses were received from training leads. The mean overall numerical scores from the trainees was 26.1 (range 24.4–28.6) for the Severn deanery, and 27.7 (range 23.9–30) for the Peninsula deanery. All trusts scored lowest in the provision of training in GIM with a mean score of 3.1 (range 2.7–3.6) in the Severn deanery, and 3.2 (range 2.8–3.9); educational support scored highest with a mean score of 4.4 (range 3.4–4.8) for the Severn deanery and 4.3 (range 3.6–4.8) for the Peninsula deanery. Trainer scoring of the trainee experience exceeded that reported by registrars with the exception of one trust, where the scoring was equal. The mean overall numerical scores from the training leads was 29.7 (range 28.3–32.2) for the Severn deanery, and 29.4 (range 28.1–30.6) for the Peninsula deanery. Conclusion: Creation of a new survey achieved a good response rate and generated gastroenterology specific outcomes, and relevant data. This method of assessing training facilitates informed feedback to trusts and an accurate assessment of training from the perspective of both training leads and trainees. The methodology is reproducible and allows for comparative assessment.